2018
DOI: 10.1016/j.gene.2017.10.064
|View full text |Cite
|
Sign up to set email alerts
|

Female Fabry disease patients and X-chromosome inactivation

Abstract: Fabry disease is an X-linked inherited lysosomal storage disorder caused by mutations in the gene encoding α-galactosidase A (GLA). Once it was thought to affect only hemizygous males. Over the last fifteen years, research has shown that most females carrying mutated allele also develop symptoms, demonstrating a wide range of disease severity, from a virtually asymptomatic to more classical profile, with cardiac, renal, and cerebrovascular manifestations. This variable expression in females is thought to be in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 33 publications
3
36
0
2
Order By: Relevance
“…Tanakahashi N et al reported that a middle-aged woman with normal GLA enzyme activity was diagnosed with FD by kidney pathology [34]. For a heterozygous female, X chromosome inactivation means there is no clear association between clinical symptoms and GLA enzyme activity [35]. In female FD patients, the enzymatic activity can be normal or slightly lower.…”
Section: Discussionmentioning
confidence: 99%
“…Tanakahashi N et al reported that a middle-aged woman with normal GLA enzyme activity was diagnosed with FD by kidney pathology [34]. For a heterozygous female, X chromosome inactivation means there is no clear association between clinical symptoms and GLA enzyme activity [35]. In female FD patients, the enzymatic activity can be normal or slightly lower.…”
Section: Discussionmentioning
confidence: 99%
“…Variants in this gene can affect enzyme synthesis, folding, degradation, trafficking or activity, leading to inability to degrade Gb3. Males have low or absent enzyme activity, but as a result of the lyonization process (transcriptional inactivation of one of the X chromosomes in some cells during embryogenesis) may present with atypical forms and a wide spectrum of signs and symptoms ( Figure 12 ), depending on enzyme’s activity preservation or absence among the different organs and tissues 49 .…”
Section: Intracellular Deposit Storage Diseasesmentioning
confidence: 99%
“…XCI status has been used to explain the wide spectrum of phenotypes observed (from asymptomatic to severe) in some X‐linked diseases in women, depending on the degree of silencing of the normal allele (Echevarria et al, 2016; Elstein, Schachamorov, Beeri, & Altarescu, 2012; Fahim et al, 2019; Juchniewicz et al, 2018). For example, the severity scores and progression phenomena in X‐linked Fabry disease caused by α‐Gal deficiency had significant correlation with XCI ratio in female patients (Echevarria et al, 2016; Elstein et al, 2012; Juchniewicz et al, 2018). Given the recent observation that skewed XCI is common in the general female population (Shvetsova et al, 2019), female patients with clinical features of an X‐linked recessive disorder and one copy of the mutated gene should be screened for skewed XCI.…”
Section: Discussionmentioning
confidence: 99%